Mesto tocnosti dvizenij v strukture fiziceskich kacestv - Nemcev, O. B. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The place of precision in the structure of physical characteristics still not determined. It is caused by the absence of the objective criterion of the classification of physical characteristics in many aspects. Such criterion can be the qualitative sides of the motor activity. From the offered by the author position, the physical characteristic of a human - it is his ability to motor activity. It's mechanical part has the certain objective qualitative description. The necessary and the sufficient characteristics of the motor activity are: 1) physical characteristics of a mechanical movement (speed, power, work, capacity); 2) characteristics of the conformity of parameters of a movement with its purpose (conformity of spatial characteristics and systems of movements). It provides the logic allocation of the following physical characteristics: speed, power, endurance, capacity, precise and coordination.